Unveiling the Enigma: Exploring Regulated Marriage Age Limits from the Lens of Maslahah Mursalah - Abdullah, Zaitun; Putri Ayu Maharani (Nurani, 2024)
The purpose of this research is to ensure that the principle of maslahah mursalah should serve as the foundation for the formation of Islamic Law in terms of regulating changes that occur in society. The Indonesian government recently revised the minimum age for a woman to marry from 16 to 19 years.  This inevitably gives rise to new complications in society, as can be seen from the large number of requests for marriage dispensations submitted to the Syariah Courts. This complication arises because if the marriage continues to be carried out under age then the marriage will become invalid. The emergence of a new regulation that regulates the age limit for a person to enter into a marriage has given rise to the author's enigma about whether it is in accordance with the concept of presenting maslahah mursalah in society or vice versa? To address the  issues that arise, researchers use the data collection method employed in this research is the interpretative understanding constructivist approach with a phenomenological framework, primary data obtained in the Babelan, Bekasi. While secondary data were derived from the examination of ten Syariah Court Judges' rulings on underage marriage petitions and existing literature. The conclusion of this research is that the implementation of the Marriage Law which regulates the age limit for marriage is considered to have not been able to reduce the number of underage marriages. In terms of implementing these rules it is very weak and does not provide any benefits (maslahah mursalah) for the community, because the government was not serious about carrying out socialization about this matter. Consequently, this regulation falls short in safeguarding the community's welfare.